Centralized management of Islamic philanthropy at LAZISMU Banyumas: Enhancing welfare through community-based innovation in Indonesia - Makhrus, Makhrus; Sulaeman, A. (Journal of Islamic Economics Lariba, 2025)
IntroductionIslamic philanthropy has great potential to improve the welfare of society, especially in Muslim-majority countries. However, the management of Islamic philanthropy funds is often fragmented, less transparent, and poorly coordinated, reducing its effectiveness. Therefore, an innovative management approach is needed, one of which is through a centralized system that can improve the efficiency, transparency, and accountability of Islamic philanthropy management.ObjectivesThis article aims to analyze the role of centralized systems in the management of Islamic philanthropy by explaining how management innovations can improve the effectiveness of the collection, distribution, and impact of Islamic philanthropic funds as practiced by community-based Islamic philanthropic organizations.MethodUsing a qualitative research with a descriptive approach, while techniques using structured interviews, observation, and documentation regarding the application of centralized management of Islamic philanthropic organizations. Data analysis is done qualitatively with deductive and inductive methods.ResultsThe innovation of Islamic philanthropy management using a centralized system has been able to improve the accountability and transparency of philanthropic fund management. The positive impact on community welfare can be seen through more targeted programs, such as education, da'wah, health, and economic empowerment. In addition, the level of public trust (muzaki and mustahik) in Islamic philanthropy institutions continues to increase due to digital reporting.ImplicationsThis study contributes to three areas: policy makers, where the government and religious authorities need to encourage the standardization of a centralized system for Islamic philanthropy. Islamic philanthropic organizations, to centralize and digitize to maintain transparency in the management of Islamic philanthropic funds. The public, increasing awareness of the importance of well-managed philanthropy by encouraging greater participation.Originality/NoveltyThis study contributes to adding to the literature in Islamic philanthropy management by focusing on centralized governance innovation, thus offering insight and understanding that innovation is an absolute institutional matter to maintain the sustainability of Islamic philanthropy organizations.